2020
DOI: 10.3759/tropics.ms19-07
|View full text |Cite
|
Sign up to set email alerts
|

Local perceptions of forest rules and interactions between rules, ecotourism, and human-wildlife conflicts: Evidence from Chitwan National Park, Nepal

Abstract: There is always a conflict of interest between conservation efforts and communities living near conservation areas. Buffer zones and opportunities for ecotourism are sometimes created to lessen the negative impact of the stringent rules involved in conservation which directly impacts the livelihoods of neighbouring communities. This paper examines a Nepalese community s perceptions of the Buffer Zone Community Forest (BZCF) rules, and investigates the interplay of rules, ecotourism, and human-wildlife conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Thus the “rules” includes a fundamental shift from exclusionary to inclusive conservation through the devolution of some aspects of wildlife proprietorship (Schlager & Ostrom, 1992), the establishment of community organization in the form of participatory governance (Child, 2019), and much more frequent and respectful relationships between the game park and the community (Durant et al, 2022). Our findings are consistent with recent literature demonstrating that the legitimacy of, agreement with, or respect for, local conservation regulations improves compliance with conservation rules (Kahler & Gore, 2012; Kandel et al, 2020) and reinforces positive perceptions of conservation (Ntuli et al, 2019). Together, this emphasizes the importance of including institutions in the definition and discussion of coexistence.…”
Section: Discussionsupporting
confidence: 92%
“…Thus the “rules” includes a fundamental shift from exclusionary to inclusive conservation through the devolution of some aspects of wildlife proprietorship (Schlager & Ostrom, 1992), the establishment of community organization in the form of participatory governance (Child, 2019), and much more frequent and respectful relationships between the game park and the community (Durant et al, 2022). Our findings are consistent with recent literature demonstrating that the legitimacy of, agreement with, or respect for, local conservation regulations improves compliance with conservation rules (Kahler & Gore, 2012; Kandel et al, 2020) and reinforces positive perceptions of conservation (Ntuli et al, 2019). Together, this emphasizes the importance of including institutions in the definition and discussion of coexistence.…”
Section: Discussionsupporting
confidence: 92%
“…The data indicated that 51% of respondents believed IUCs consumption was in an increasing trend, whereas 30% of respondents felt the consumption decreased and the remaining viewed the constant consumption trend (Figure 6). During COVID-19, due to transportation halt, agricultural-product damaged and food supply affected (Kandel et al, 2020). As a coping strategy, people consumed indigenous and underutilized crops to sustain their life.…”
Section: Consumption Trend Of Iucs In Recent Yearsmentioning
confidence: 99%
“…Current studies have found different perceptions and attitudes towards ecotourism activities (Juvan and Dolnicar 2016 ). The main phenomena involve negative effects experienced by the local inhabitants as a result of interactions with tourists coming to the region (Muresan et al 2016 ; Kandel et al 2020 ). Some studies have shown that this situation negatively affects the development of ecotourism and recreational activities (Cakir et al 2016 ).…”
Section: Conceptual Frameworkmentioning
confidence: 99%